A study on the rheological properties and modification mechanism of graphene oxide/polyurethane/SBS-modified asphalt. - Shuai Li (PLoS ONE, 2022)
To study the effect of graphene oxide (GO) on thermoplastic polyurethane (TPU)/styrene-butadiene-styrene (SBS)-modified asphalt and reveal the modification mechanism, GO/TPU/SBS-modified asphalt was prepared by high-speed shearing Hongjuan et al. (2020). The physical properties of the modified asphalt were measured via a basic index test, and the dynamic rheological behavior of the modified asphalt was characterized by a dynamic shear rheometer (DSR), a bending beam rheometer (BBR), and other technical means. Moreover, double-beam UV-visible (UV-Vis) spectrophotometry and Fourier-transform infrared spectroscopy (FTIR) were conducted to determine the mechanism of asphalt modification from the microscopic perspective. The experimental results reveal that the GO content can improve the basic mechanical properties, high-temperature stability, and low-temperature cracking resistance of TPU/SBS-modified asphalt. When the GO content is 0.5%, the ductility and softening point of the modified asphalt are found to be significantly increased, and the degree of penetration is slightly decreased. Moreover, with the increase of the GO content, the rutting resistance and crack resistance of the asphalt materials are improved. Via the joint action of physical modification and chemical reaction, GO can form a stable structure with asphalt molecules, enhance the stability between asphalt molecules, and increase the colloidal content of macromolecules in the modified asphalt components.